Numerical analysis of MIMO FM-CW radar performance using beat signal averaging / Asiah Maryam Md Noor … [et al.] - Md Noor, Asiah Maryam; Pasya, Idnin; Abd Rashid, Nur Emileen; Zainuddin, Suraya; Abdullah, Abdul Rahman (UiTM Press, 2023)
Radar for years has been used as the typical instrument in maritime surveillance especially in border security. However, there is yet a big challenge in maritime radars to be resilient against the large clutter of the seawaves, which produces a low signal-to-noise ratio (SNR) environment. This paper proposes the approach of beat signal averaging method to imply multiple-input multiple-output (MIMO) configuration on frequency modulated continuous wave (FM-CW) radar system in maritime environment. The system works by the basis of transmitting multiple FMCW signal with different frequencies and bandwidth, and formulating multiple beat signals from each of the transmitted signals at the receiver. Then, beat signals averaging was conducted prior to peak detection and range estimation. This method is proposed to improve the ranging accuracy, especially when working SNR is low. A numerical simulation was performed to study the performance of the proposed method in terms of target ranging error probability against low SNR. It was found that higher order MIMO scheme of the radar system shows better accuracy for range estimation. The performance of the proposed radar was further explored by comparing with existing method such as spectrum averaging, and their computational complexity was also analyzed.